2016
DOI: 10.1515/med-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic GSV surgery in elderly candidates for hip or knee arthroplasty

Abstract: AbstractAging is one of the major risk factors for varicose veins. The same is for Knee and Hip Osteoarthritis. Most of the patients undergoing to Hip (THA) or Knee (TKA) arthroplasty are over sixteen. Varicose veins, excluding thrombophilia, are the most significant risk factors for VTE after THA and TKA.This study investigates on the usefulness of prophylactic treatment of GSV insufficiency in elderly patients undergoing to orthopedic surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…There is no consensus on the need for preliminary surgical treatment of varicose veins to reduce the risk of postoperative VTE. Limited evidence suggests that patients with treated VV may normalize their VTE risk after THA and TKA 259,266 . This risk may be mitigated by VTE prophylaxis, although current studies on VTE prophylaxis for orthopaedic procedures did not analyze the efficacy of preventive measures in this small subgroup of patients with VV and hence no conclusion can be drawn.…”
Section: - Does the Presence Of Varicosities And/or Superficial Lower...mentioning
confidence: 99%
“…There is no consensus on the need for preliminary surgical treatment of varicose veins to reduce the risk of postoperative VTE. Limited evidence suggests that patients with treated VV may normalize their VTE risk after THA and TKA 259,266 . This risk may be mitigated by VTE prophylaxis, although current studies on VTE prophylaxis for orthopaedic procedures did not analyze the efficacy of preventive measures in this small subgroup of patients with VV and hence no conclusion can be drawn.…”
Section: - Does the Presence Of Varicosities And/or Superficial Lower...mentioning
confidence: 99%
“…Collectively, 2188 patients had varicose veins as per the studies included in this review. [10][11][12][13][14][15][16][17][18][19][20][21][22] Overall, the clinical detail surrounding these patients with concurrent venous disease is sparse, with no reference made to the severity of disease, and only one study investigating the effect of previous varicose vein surgery and the effect on VTE risk. The incidence of post-operative VTE in orthopedic patients with varicose veins stated in the relevant studies ranges from potentially beneficial at reducing VTE risk, however, the results are not statistically significant and more evidence is necessary to come to better conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…When prophylactically managing varicose veins with great saphenous vein surgery or endovenous laser ablation, Quarto et al demonstrated a reduced risk of arthroplasty-related DVT and VTE compared to reference studies. 6,27 Comparably, in an attempt to determine if morbid obesity was an independent risk factor for TKA complications, D'Apuzzo et al showed that obesity significantly increased postoperative in-hospital infection (OR ¼ 1.3), genitourinary complication (OR ¼ 1.3), total hospital costs (USD 15,174 vs. USD 14,715, p < 0.001), and LOS (3.6 vs. 3.5 days, p < 0.001). These findings, similar to those of our current study, were aimed to define an independent risk factor for TKA complications, adverse outcomes, and resource use, which led to increased understanding of a previously understudied area in orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Patients suffering from venous insufficiency have complications including leg pain, skin changes, nonhealing ulcers, and edema and are at increased risk for deep vein thrombosis (DVT) and venous thromboembolism (VTE). 5,6 The pathophysiology of CVI leads to ambulatory venous hypertension, venous reflux, and impaired tissue perfusion and oxygen diffusion, all of which can lead to wound healing issues postoperatively. 7,8 Preexisting CVI is associated with increased adverse events and decreased patient satisfaction following procedures such as open treatment of ankle fractures and plastic reconstructive surgery of the lower extremity.…”
mentioning
confidence: 99%